Epistemological Foundations of Maharah Qira’ah Learning in Arabic Language Education - Nayogi, Siti Zahrah; Sholiha, Mar’a Aqila; Mukaromah, Zahrotul (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
Reading skills play a central role in Arabic language learning as the main pathway to understanding classical and contemporary texts. Yet, instruction often remains limited to technical decoding without fostering critical comprehension. This article outlines the epistemological foundations needed to develop mahārah qirā’ah so that Arabic learning becomes more systematic and meaningful. Using a qualitative literature review, data were drawn from journals, books, and Arabic texts as primary sources. Ontologically, mahārah qirā’ah     is not merely pronunciation but the ability to link linguistic symbols with conceptual and civilizational knowledge. Epistemologically, its mastery involves layered processes: textual sources analyzed through grammar, semantics, and context; stages of acquisition including perceptual (empirical), cognitive (rational), interpretative (hermeneutical), validative (epistemic), and applicative (pragmatic); and validation through linguistic, semantic, hermeneutic, and metacognitive criteria. Innovative methods such as Jigsaw, Inquiry, and Contextual Teaching and Learning help integrate these dimensions. In conclusion, an epistemological approach elevates mahārah qirā’ah     from technical skill to critical, reflective thinking, ensuring valid and coherent understanding aligned with modern educational demands